Physiological and Biochemical Responses of Rice (Oryza Sativa L.) Varieties Against Drought Stress (Bangladesh Journal of Botany, 2021)
Physiological and biochemical responses of six different rice (Oryza sativa L.) varieties cultivated in Turkey and two local varieties, namely Karacadağ and Hazro to the drought were investigated. After 12 days of drought treatment, the highest and lowest OP values were observed in Osmancık-97 (-1.14 MPa) and Karacadağ (-1.55 MPa) varieties, respectively. In the same treatment, it was observed that the amount of proline increased 19.9-fold in Karacadağ and 3.6-fold in Osmancık-97. When the data obtained from all parameters were correlated with drought stress tolerance, Osmancık-97 and Beşer varieties were considered to be tolerant, while Gönen and Karacadağ varieties are considered to be more sensitive.Bangladesh J. Bot. 50(2): 335-342, 2021 (June)